Examining Green Marketing at The Creative Industry in Economic Recovery - Luh Gde Intan Pradnyamita; Gede Sri Darma (Jurnal Manajemen dan Bisnis, 2022)
The Coronavirus Disease 2019 (COVID-19) is expected to infect millions of people all over the world.Indonesia has fallen into recession because of it. The economic crisis due to the Covid-19 pandemic hasshown the importance of economic development by paying attention to environmental sustainability.The solution that can be done to increase the economy is through the development of creativeindustries. This study aims to determine the understanding of creative industry managers in the fashion,craft, and culinary sectors regarding green marketing and the practice of implementing green marketing in the creative industry during the economic recovery. This descriptive qualitative study shows that thecreative industry which has a big role in increasing the national economy can start by understanding themeaning of green marketing itself first so that it can apply it well to their company. This study can guidefor creative industry managers, especially creative industries in the fashion, craft, and culinary sectorsto create a sustainable economy by implementing green marketing in their companies.